Inclusion Through Participation: Understanding Participation in the International Classification of Functioning, Disability, and Health as a Methodological Research Tool for Investigating Inclusion - Maxwell, Gregor R.; Granlund, Mats; Augustine, Lilly (Frontiers in Education, 2018)
This paper investigates the use and validity of the International Classification of Functioning disability and health (ICF) as a common language for describing inclusive educational settings. There is a specific focus on investigating participation through the ICF as one aspect of inclusion as an improved understanding of participation as a measure of inclusion will greatly benefit children with additional support needs. In addition there will be a better understanding of the operationalization of participation, in terms of both policy and practice, and improved applications of the ICF. The study uses a narrative summary to review to analyse the findings from a selection of studies where the ICF has been used as a methodological tool in the field of education. In the 16 included studies the ICF is either used to present a new theoretical position, synthesize a new research approach or tool, or is integrated into the framework of an existing research method. Findings also show that the ICF is used in a number of different ways and that when it is used directly, variation is found in the type of information that was linked to ICF codes or categories. In conclusion further clarity on defining and measuring participation with the ICF framework is required in order to create a more consistent tool for investigating inclusive education. One way to improve the construct of participation is to take a bi-dimensional approach. It is the authors’ belief that this newer approach to modelling participation will be considered in any future revisions of the ICF/ICF-CY – a so-called ‘ICF-2’. This would thus create a more accountable classification framework that succeeds in capturing the involvement experience of the individual and in doing so achieves a more effective and useful classification framework for the field of inclusive education.